Impact of floral density on pollination success rate and fruit set of Calceolaria gracilis Kunth in Darjeeling Himalaya - Bhattacharya, Ashoke (Current Botany, 2017)
There are many populations in a 16 km east-west distribution and populations are usually small with fewer than 100 plants/clumps. The pollen biology in terms of pollen production, pollen-ovule ratio estimation, pollen viability and pollen fertility was studied to determine the impact of plant and flower density on pollen viability and fruit set of Calceolaria tripartita Ruiz &Pav. (Scrophulariaceae) in Darjeeling Himalaya. It is revealed that higher the density of the plants and flowers, the productivity of pollens and ovules and the viability and fertility of pollen grains become higher showing a positive correlation between plant-flower density vs. pollen biology. Fruit set is higher in high dense flowering site than low ones which might be due to higher pollen fertility rate, low sterility and greater number of pollen load upon stigma. Thus, it reflects that plant and flower density has a crucial role upon the reproductive fitness of this taxon.